Initiation of phi 29 DNA replication occurs at the second 3' nucleotide of the linear template: a sliding-back mechanism for protein-primed DNA replication. - Méndez, J (1992)
Bacteriophage phi 29 DNA replication is initiated when a molecule of dAMP is covalently linked to a free molecule of the terminal protein, in a reaction catalyzed by the viral DNA polymerase. We demonstrate that single-stranded DNA molecules are active templates for the protein-primed initiation reaction and can be replicated by phi 29 DNA polymerase. Using synthetic oligonucleotides, we carried out a mutational analysis of the phi 29 DNA right end to evaluate the effect of nucleotide changes at the replication origin and to determine the precise initiation site. The results indicate that (i) there are no strict sequence requirements for protein-primed initiation on single-stranded DNA; (ii) initiation of replication occurs opposite the second nucleotide at the 3' end of the template; (iii) a terminal repetition of at least two nucleotides is required to efficiently elongate the initiation complex; and (iv) all the nucleotides of the template, including the 3' terminal one, are replicated. A sliding-back model is proposed in which a special transition step from initiation to elongation can account for these results. The possible implication of this mechanism for the fidelity of the initiation reaction is discussed. Since all the terminal protein-containing genomes have some sequence reiteration at the DNA ends, this proposed sliding-back model could be extrapolable to other systems that use proteins as primers.